Simple view on fingering instability of debonding soft elastic adhesives - Vilmin, Thomas; Ziebert, Falko; Raphaël, Elie (Langmuir, 2010)
We study the crack-front fingering instability of an elastic adhesive tape that is peeled off a solid substrate. Our analysis is based on an energy approach using fracture mechanics and scaling laws and provides simple physical explanations for (i) the fact that the wavelength depends only on the thickness of the adhesive film and (ii) the threshold of the instability, and (iii) additionally estimates the characteristic size of the fingers. The scaling laws for these three observables are in agreement with existing experimental data.
Published on web 10/06/2009
Gesehen am 23.09.2022